Un tipo de lectura profesional: los humanistas y los textos - Jiménez Calvente, Teresa (2014)
Para el Humanismo cuatrocentista, el estudio de la Antigüedad suponía la lectura directa de los originales latinos y griegos. Entre el profesional de las letras y el simple neófito, ese ideal desembocó en una determinada propedéutica y animó un mercado del libro que pretendía satisfacer a un público tan diverso.
Fifteenth -Century humanists encouraged a direct approach to the Classics, a method based on the reading of both Latin and Greek originals. This diversity of readers, between the professionals of letters and first-year students, explains most changes and progresses in two closely related cultural fields: propedeutics and book industry.
Keywords: Humanismo; Lectura